Effectiveness and Safety of Direct Oral Anticoagulants in Relation to Temporal Changes in Their Use. Issue 3 (March 2020) - Lee, So-Ryoung; Choi, Eue-Keun; Kwon, Soonil; Jung, Jin-Hyung; Han, Kyung-Do; Cha, Myung-Jin; Oh, Seil; Lip, Gregory Y.H.
Abstract : Background: Since the direct oral anticoagulants (DOAC) were introduced, oral anticoagulant (OAC) prescription patterns have rapidly changed in patients with atrial fibrillation (AF). We aimed to evaluate the evolving trends of OAC use in a large nationwide cohort and specifically examine the changes in patient profiles treated with warfarin or DOAC and whether the time trends in OAC use affected clinical outcomes. Methods and Results: Using the Korean Health Insurance Review and Assessment database, we divided OAC naive patients with AF into 3 groups according to the enrollment period between January 2015 and December 2017 (n=35 353 in cohort 1, n=36 631 in cohort 2, and n=44 819 in cohort 3). DOAC use increased from 59% to 89%, whereas warfarin use has decreased from 41% to 11% during the study period. Patients treated with warfarin were increasingly younger from cohort 1 to cohort 3 (mean age 68–65 years, P <0.001) with lower mean CHA2 DS2 -VASc scores (3.3–2.9, P <0.001), whereas those with DOAC did not show a significant difference in clinical characteristics over the study period. Warfarin group had improved clinical outcomes over time, reflecting dynamic changes in patient characteristics. Compared with warfarin group, unadjusted hazard ratios of composite outcome for DOAC group have changed over time (hazard ratio 0.77 [95% CI, 0.69–0.85] in cohort 1, hazard ratio 0.84 [95% CI, 0.73–0.97] in cohort 2, and hazard ratio 1.00 [95% CI, 0.78–1.25] in cohort 3). After propensity score weighting between warfarin and DOAC groups in each cohort, DOAC showed consistently lower risks of the composite outcome by approximately 23% to 25% compared with warfarin across 3 different periods. Conclusions: In contemporary clinical practice, OAC prescription patterns and characteristics of patients treated warfarin or DOAC have dynamically changed. Despite these changes, DOAC showed a consistent better net clinical benefit compared with warfarin across different periods. Abstract : Supplemental Digital Content is available in the text.